Molecular and expression analyses indicate the role of fusion transcripts in mediating abiotic stress responses in chickpea - Hamid, Fiza; Zahra, Shafaque; Kumar, Shailesh (Frontiers in Plant Science, 2025)
Understanding the transcriptome diversity is essential for deciphering the transcriptional level regulation. High-throughput sequencing technologies have facilitated the detection of fusion transcripts (FTs), which are chimeric mRNA molecules derived from gene fusions due to chromosomal rearrangements or via the splicing machinery at the RNA level. In this study, we investigated the transcriptome complexity in Cicer arietinum resulting from fusion events using high-throughput RNA-Seq datasets from five tissues, i.e., stem, leaves, buds, flowers, and pods, and two abiotic stress conditions, i.e., drought and salinity. Of the 328 unique FTs identified, 69% exhibited the presence of canonical splice sites at their junction, indicating their generation via trans-splicing. Functional annotation and enrichment analyses of fusion partners suggested that these transcripts may expand functional diversity. A total of 10 FTs were validated via RT-PCR followed by Sanger sequencing, which are the first FTs described in the important legume chickpea. Expression analysis of fusion transcripts across various tissues and under abiotic stress conditions revealed evidence of context-dependent regulation. Furthermore, 120 fusion gene pairs were found to be conserved across 17 chickpea genotypes, highlighting their potential biological significance and stability within the species. Overall, these findings suggest that fusion transcripts may contribute to regulatory mechanisms underlying abiotic stress responses in chickpea.